2002
DOI: 10.1097/00003072-200211000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Post-therapeutic Lymphedema: Scintigraphy Before and After Autologous Lymph Vessel Transplantation

Abstract: The function of lymphatic vessel grafts was proved in 12 patients with lymphedema of the upper extremity by visual and semiquantitative evaluation of a preoperative baseline study and scintigraphic follow-up data for a period of 8 years after microsurgical treatment. The transplantation site was an upper extremity. In 11 of 12 patients, lymphatic function improved after autologous lymphatic vessel transplantation compared with preoperative findings. This could be verified by a statistically significant decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 6 publications
1
34
0
3
Order By: Relevance
“…5,8,9,13,14,17,19,[22][23][24] The findings in our patients confirmed these authors, but the condition and level of the remaining lymphatics is very difficult to estimate preoperatively with clinical or scintigraphic findings, and the timing of the occlusion and degeneration of the smooth muscle cells at the walls of lymphatics may not directly correspond to the duration of the edema 10 ; the stage of the disease seems to be more decisive. An intraoperative observation worth to mention here is, segmental contraction of the lymphangions, recognized clearly in four of our cases (three stage II and one stage III), may be a unique sign for a good outcome after lymphaticovenular anastomosis.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…5,8,9,13,14,17,19,[22][23][24] The findings in our patients confirmed these authors, but the condition and level of the remaining lymphatics is very difficult to estimate preoperatively with clinical or scintigraphic findings, and the timing of the occlusion and degeneration of the smooth muscle cells at the walls of lymphatics may not directly correspond to the duration of the edema 10 ; the stage of the disease seems to be more decisive. An intraoperative observation worth to mention here is, segmental contraction of the lymphangions, recognized clearly in four of our cases (three stage II and one stage III), may be a unique sign for a good outcome after lymphaticovenular anastomosis.…”
Section: Discussionsupporting
confidence: 79%
“…They, subsequently, argued that it was not possible to interpret the direct benefit from the surgical procedure above the improvement from compression therapy in other series where postoperative compression was used. 23 They also claimed that there are no currently available means to study lymphatic vessel patency. 11 The preoperative and postoperative volumes of the edema, the protocol of using postoperative garments (including the patients with no compression) are unequivocally presented in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To exemplify the results of LVA, we chose objective outcome parameters for improvement of lymphtransport capacity, volume changes and quality of life. Kleinhans et al demonstrated the usefulness of the Transport Index to evaluate the results of lymphatic grafting [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Fehlbefunde k ö nnen durch Vermeidung einer intravasalen Applikation des Radiopharmakons verhindert werden [8,15,24,26,27,30,31,46,48] . Zudem kann als Therapiekontrolle ü ber viele Jahre hinweg eine persistierende Funktion der Lymphgef ä ß transplantate durch die lymphszintigrafi sche Bildgebung im Vergleich zum pr ä operativen Zustand dokumentiert werden [5,42,43] . Bei einer ü ber die Beurteilung mittels Transportindex hinausgehende Quantifi zierung des Lymphabtransportes mittels Regions-of-Interest, muss bei klinischen Untersuchungen ber ü cksichtigt werden, dass hierbei die Ergebnisse stark von der w ä hrend des Untersuchungszeitraumes ausge ü bten Muskelanstrengung seitens des Patienten abh ä ngen; letztere m ü ssen daher streng standardisiert werden.…”
Section: Diskussion and Lymphogener Transportunclassified